The Role Of Land Certificates In Civil Dispute Resolution - Firman Adi Candra (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The abstract of this study shows that land certificates have a very important role in resolving civil disputes in Indonesia. As a valid legal evidence, land certificates provide legal certainty for legitimate owners. However, there are a number of challenges in its implementation, such as the issuance of duplicate certificates, low public awareness of the importance of land registration, and administrative problems that often trigger disputes. The Complete Systematic Land Registration Program (PTSL) has had a positive impact by accelerating the issuance of certificates, but its implementation is still limited to several regions. Therefore, improvements are needed in the land administration system, public education regarding land registration, and stricter supervision of certificate issuance. Stricter law enforcement and strengthening of land policies are also needed to prevent land disputes in the future.